French Guyanan stock of Trypanosoma vivax resistant to diminazene aceturate but sensitive to isometamidium chloride - Desquesnes, M.; Rocque, S. de la; Peregrine, A.S. (Elsevier, 1995)
An isolate of T. vivax was collected from a naturally infected Zebu in French Guyana. The isolate was subsequently shown to produce pathogenic infections in both Taurine and Zebu cattle. However, its sensitivity of the population to diminazene aceturate and isometamidium chloride was determined since these are the most commonly used anti-trypanosomal compounds in French Guyana. The studies were carried out in cattle and sheep since the resultant data provide direct information about therapeutic efficacy of the anti-trypanosomal compounds in the field; sheep are suspected to act as a reservoir of T. vivax in French Guyana. According to the result of this experiment, T. vivax originating from French Guyana expresses resistance to the maximum recommended dose of diminazene but is sensitive to isometamidium chloride at a dose of 0.5 mg/kg BW.